Role of pulse oximetry in detecting critical congenital heart disease among newborns delivered at a high altitude setting in Ethiopia - Tekleab AM; Sewnet YC (Dove Medical Press, 2019)
Atnafu Mekonnen Tekleab,1 Yilikal Chanie Sewnet21Pediatrics and Child Health, St Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Cardiac Center of Ethiopia, Addis Ababa, EthiopiaBackground: Congenital heart disease is one of the most common birth defects. It is not detected in some newborns until after their hospital discharge. Pulse oximetry (SpO2) screening for critical congenital heart disease (CCHD) is practiced in some settings, mainly based on evidence derived from studies done in lowland areas. This study aimed to assess the role of SpO2 screening performed before discharge in detecting CCHD in our setting (Addis Ababa) which is located at high altitude.Methods: Oxygen saturation of 941 apparently healthy term newborns in the nursery unit of St Paul’s Hospital Millennium Medical College located in Addis Ababa, was measured before discharge during the period from January 2018 to July 2018. SpO2 reading ≥95% was taken as a negative screening result. Positive SPO2 was defined as SpO2 <90% in any extremity, or a persistent SpO2 of 90%–94% in both right arm and lower extremity sites on three measurements or a persistent right arm to lower extremity SpO2 difference of >3%. Subsequent confirmatory echocardiography examination was done for those who tested positive during the SpO2 screening test. Data were analyzed using Statistical Package for Social Sciences version 20.0.Results: A total of 56/941 (6.0%) newborns tested positive during the screening test. Of those 56 cases, subsequent echocardiography examination detected persistent pulmonary hypertension of the newborn (PPHN) in ten (17.9%) cases (subsequently two of them were found to have sepsis), patent ductus arteriosus in eleven (19.6%) cases, and atrial septal defect in two (3.6%) cases. No case of CCHD was detected among the screened newborns.Conclusion: SpO2 screening detected non-cardiac causes of hypoxemic illnesses (sepsis and PPHN) which otherwise would have been missed. However, we recommend a larger sample size study to assess the efficacy of SpO2 screening in detecting CCHD in our setting.Keywords: pulse oximetry, screening, congenital heart disease, high altitude